2012
DOI: 10.1038/pj.2012.116
|View full text |Cite
|
Sign up to set email alerts
|

Change in local dynamics of bacteriorhodopsin with retinal isomerization under pressure as studied by fast magic angle spinning NMR

Abstract: Bacteriorhodopsin (bR) has a retinal with all-trans and 13-cis, 15-syn configurations whose isomeric ratio is close to 1 in the dark-adapted bR, and the population of the 13-cis, 15-syn configuration can be increased under pressure. In our previous study, we applied pressure to bR using centrifugal force introduced by sample spinning and demonstrated that the 15 N nuclear magnetic resonance (NMR) signal intensity of the Schiff base in 13-cis, 15-syn retinal increased. In this study, we demonstrate a pressure-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In this frame, carbonic anhydrase and the catalytic domain of the MMPs have fairly low melting temperatures [84,85], suggesting a comparably low stability toward slightly harder experimental conditions (i.e. : toward the higher pressure that is possibly encountered during MAS-induced sedimentation [86]). …”
Section: Resolution and Sensitivity Of Sedimented Proteinsmentioning
confidence: 99%
“…In this frame, carbonic anhydrase and the catalytic domain of the MMPs have fairly low melting temperatures [84,85], suggesting a comparably low stability toward slightly harder experimental conditions (i.e. : toward the higher pressure that is possibly encountered during MAS-induced sedimentation [86]). …”
Section: Resolution and Sensitivity Of Sedimented Proteinsmentioning
confidence: 99%
“…The significant mechanical forces, such as centrifugal pressure, involved in MAS additionally offer a novel modulator of the amyloid formation pathway. Previous work has demonstrated the ability of small molecules, peptides, lipid membranes, metals, synthetic polymers, pH, and electric fields to alter amyloid aggregation pathways and in some cases to stabilize oligomeric intermediates for further structural studies. Pressure as a result of centrifugal forces during MAS has been found to affect the structure and dynamics of bacteriorhodopsins and apoferritin, but its effect on the species formed during amyloid aggregation has not been fully characterized. Here, we provide the first report, to the best of our knowledge, of the ability of the mechanical forces associated with MAS to stabilize intermediate, on-pathway aggregates of human islet amyloid polypeptide (hIAPP) in an aqueous environment.…”
mentioning
confidence: 87%
“…This peak was assigned to Ala81 and Ala84 which are located in the vicinity of retinal. It was observed that changes in local dynamics in the vicinity of retinal were caused by the application of pressure [168].…”
Section: Bacteriorhodopsinmentioning
confidence: 98%